PENGARUH PROFESIONALISME APARAT TERHADAP KUALITAS PELAYANAN PADA BADAN KEPEGAWAIAN DAERAH KOTA KENDARI - Bakti Bakti (Universitas Halu Oleo, 2018)
The Effect of apparatus professionalism toward service quality in the Regional Employment Affairs Kendari. The problem discussed in this research is whether apparatus professionalism has effect to service quality at the Regional Employment Affairs of Kendari City and its objective is to know the effect and how much these effects influence service quality at the Regional Employment Affairs of Kendari City. This research investigates apparatus professionalism dimension which includes: creativity, innovation, responsiveness, and also service quality dimension which includes: procedures for the service, distinctness of service personnel, discipline of service personnel, responsibility care workers, justice get service, politeness and friendliness of service personnel, certainty of service schedule , pleasant services, security services. This research is an explanatory research that examines the stated hypothesis through quantitative approaches and statistical tests. Sample in this research is 50 people who are selected randomly from the total population. Colecting data is executed using the questionnaire, interviews, and dokementasi as secondary data. Then, the quantitative data is processed by corelation product moment analysis, simple regretion analysis and normality test. The resultsof this reseacrh shows that apparatus professionalism has a significant effect towards service quality at the Regional Employment Affairs of Kendar City. Apparatus professionalism is dominant factor which influences service quality. The result shows that service quality at the Regional Employment Affairs of Kendari City will be better if the apparatus professionalism can be improved Keywords : Apparatus Professionalism, Service Quality.